Blockade of voltage-dependent K+ current in rabbit coronary arterial smooth muscle cells by the tricyclic antidepressant clomipramine - Hongliang Li; Sung Eun Shin; Jin Ryeol An; Mi Seon Seo; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Amy L. Firth; Dae-Sung Lee; Mi-Jin Yim; Jeong Min Lee; Grace Choi; et al. (Elsevier, 2018)
We investigated the effect of the tricyclic antidepressant clomipramine on voltage-dependent K+ (Kv) channels in native rabbit coronary arterial smooth muscle cells. Our results showed that clomipramine inhibited vascular Kv channels in a concentration-dependent manner, with an IC50 value of 8.61 ± 4.86 μM and a Hill coefficient (n) of 0.58 ± 0.07. The application of 10 μM clomipramine did not affect the activation curves of the Kv channels; however, the inactivation curves of the Kv channels were shifted toward a more negative potential. The clomipramine-induced inhibition of Kv currents was not changed by the application of train pulses (1 or 2 Hz), which demonstrated that clomipramine inhibited Kv current in a state (use)-independent manner. Pretreatment with the Kv1.5 and Kv2.1 inhibitors, DPO-1 and guangxitoxin, respectively, partially reduced the clomipramine-induced inhibition of Kv currents. Therefore, we concluded that clomipramine inhibited vascular Kv channels in a concentration-dependent, but state (use)-independent manner, regardless of its own function. Keywords: Clomipramine, Voltage-dependent K+ channel, Coronary artery